The Role of Teachers in Developing Creativity In Elementary School Age Children - Pasha, Nazwa; Arwila; Ramadhani, Jopani; Mirza, Raifan Syafiq; Utami, Tri Setia; Siregar, Hapni Laila (International Journal of Asian Education, 2025)
The purpose of this study is to analyze the role of elementary school teachers in fostering creativity in student learning development through the application of innovative learning methods and contextual learning environments. This research employs a descriptive quantitative approach involving 30 fifth-grade students from three schools SDN 106161 Laut Dendang, SDS Nahdlatul Ulama Medan, and SD Addini Medan Tembung and one teacher respondent from each school. Data were collected through creativity questionnaires distributed to students and interviews conducted with fifth-grade teachers to understand their roles and strategies in promoting creativity. The results showed that students’ learning creativity was in the moderate to quite good category, with average scores of 66.6% at SDN 106161 Laut Dendang, 62.5% at SDS Nahdlatul Ulama Medan, and 71.8% at SD Addini Medan Tembung. Based on the teacher interviews, it was found that teachers serve as facilitators, motivators, and innovators who encourage students to think critically, explore new ideas, and express their creativity freely in the classroom. The findings imply that teachers’ active participation and innovative teaching strategies play an important role in enhancing students’ creative abilities. Therefore, strengthening professional development for teachers and improving collaboration between schools and families are necessary to create a more supportive learning environment. The implications of this study emphasize the importance of integrating contextual and project-based learning to nurture students’ creativity and problem-solving skills. Additional materials used include creativity questionnaire sheets, teacher interview guidelines, and classroom documentation that support the validity of the findings.